A Pilot Study of Non-invasive Sacral Nerve Stimulation in Treatment of Constipation in Childhood and Adolescence - Besendörfer, Manuel; Kohl, Martin; Schellerer, Vera; Carbon, Roman; Diez, Sonja (Frontiers in Pediatrics, 2020)
Background/Aims: Constipation shows both, a high prevalence and a significant impact. However, it is often perceived as minor and treatment choices are limited. The neuromodulation approach is a valuable option to be considered. This study assesses the use of non-invasive sacral nerve stimulation to reduce constipation in children. Methods: Between February 2013 and May 2015, pediatric patients with chronic constipation were treated with this non-invasive neuromodulation procedure, adapted from classical sacral nerve stimulation. A stimulation device attached to adhesive electrodes on the lower abdomen and back generated an electrical field with a stable frequency of 15 Hz via variable stimulation intensity (1–10 V). The effect of therapy was evaluated in routine check-ups and by specialized questionnaires. Results: The study assessed non-invasive sacral nerve stimulation in 17 patients (9 boys, 8 girls, mean age 6.5 years). They underwent stimulation with 6–9 V for a mean of 11 h per day (range 0.5–24 h) over a mean of 12.7 weeks. Improvement of constipation was achieved in more than half of the patients (12/17) and sustained in almost half of these patients (5/12). Complications were minor (skin irritation, electrode dislocation). Conclusions: Non-invasive sacral nerve stimulation appears to be effective in achieving improvement in pediatric patients with chronic constipation. As an additional external neuromodulation concept, this stimulation may represent a relevant addition to currently available therapeutic options. Further studies are needed to confirm these results.
CRIS-Team Scopus Importer:2020-05-08
Keywords: electrostimulation; Hirschsprung's disease; non-invasive sacral nerve stimulation; pediatric surgery; slow-transit constipation

Population-Attributable Fractions of Modifiable Lifestyle Factors for CKD and Mortality in Individuals With Type 2 Diabetes: A Cohort Study - Dunkler, Daniela; Kohl, Martin; Teo, Koon K.; Heinze, Georg; Dehghan, Mahshid; Clase, Catherine M.; Gao, Peggy; Yusuf, Salim; Mann, Johannes; Oberbauer, Rainer (American Journal of Kidney Diseases, 2016)
BACKGROUND: We quantified the impact of lifestyle and dietary modifications on chronic kidney disease (CKD) by estimating population-attributable fractions (PAFs). STUDY DESIGN: Observational cohort study. SETTING & PARTICIPANTS: Middle-aged adults with type 2 diabetes but without severe albuminuria from the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial (ONTARGET; n=6,916). FACTORS: Modifiable lifestyle/dietary risk factors, such as physical activity, size of social network, alcohol intake, tobacco use, diet, and intake of various food items. OUTCOMES: The primary outcome was CKD, ascertained as moderate to severe albuminuria or ≥5% annual decline in estimated glomerular filtration rate (eGFR) after 5.5 years. The competing risk for death was considered. PAF was defined as the proportional reduction in CKD or mortality (within 5.5 years) that would occur if exposure to a risk factor was changed to an optimal level. RESULTS: At baseline, median urinary albumin-creatinine ratio and eGFR were 6.6 (IQR, 2.9-25.0) mg/mmol and 71.5 (IQR, 58.1-85.9) mL/min/1.73m(2), respectively. After 5.5 years, 704 (32.5%) participants developed albuminuria, 1,194 (55.2%) had a ≥5% annual eGFR decline, 267 (12.3%) had both, and 1,022 (14.8%) had died. Being physically active every day has PAFs of 5.1% (95% CI, 0.5%-9.6%) for CKD and 12.3% (95% CI, 4.9%-19.1%) for death. Among food items, increasing vegetable intake would have the largest impact on population health. Considering diet, weight, physical activity, tobacco use, and size of social network, exposure to less than optimum levels gives PAFs of 13.3% (95% CI, 5.5%-20.9%) for CKD and 37.5% (95% CI, 27.8%-46.7%) for death. For the 17.8 million middle-aged Americans with diabetes, improving 1 of these lifestyle behaviors to the optimal range could reduce the incidence or progression of CKD after 5.5 years by 274,000 and the number of deaths within 5.5 years by 405,000. LIMITATIONS: Ascertainment of changes in kidney measures does not precisely match the definitions for incidence or progression of CKD. CONCLUSIONS: Healthy lifestyle and diet are associated with less CKD and mortality and may have a substantial impact on population kidney health.
EVALuna2:33866